2020
DOI: 10.1088/1757-899x/877/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Stand-off Distance and of the Layers Thickness on the Adhesion and Porosity of the 97MXC Deposits Obtained by Arc Spraying Process

Abstract: In this paper, the surfaces of some weakly alloyed steel specimens were covered, by arc spraying process, with a layer of high alloyed steel: 97MXC, using core wires. The technological parameters, used to spray the high alloy steel, were kept constant except for the spray stand-off distance (SOD) which varied on three levels. The research was performed on deposits with a thickness between 0.2-2.4 mm. The microstructure of the deposits, the chemical composition, the physical properties of the layers were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The adherence of the deposits obtained by thermal spraying is defined as being the force necessary detaching the layer from the substrate. The studies carried out by Haraga et al [47] have demonstrated that the adhesion of the coatings is predominantly mechanical and is due to the solidification of the sprayed liquid particles or to the deformation of the semi-viscous particles on the substrate asperities. The adhesion of the deposits was determined by the traction test -in accordance with EN 582.…”
Section: Analysis Of 97mxc Coatings Adhesionmentioning
confidence: 99%
“…The adherence of the deposits obtained by thermal spraying is defined as being the force necessary detaching the layer from the substrate. The studies carried out by Haraga et al [47] have demonstrated that the adhesion of the coatings is predominantly mechanical and is due to the solidification of the sprayed liquid particles or to the deformation of the semi-viscous particles on the substrate asperities. The adhesion of the deposits was determined by the traction test -in accordance with EN 582.…”
Section: Analysis Of 97mxc Coatings Adhesionmentioning
confidence: 99%
“…Currently, the development of the industrial world is experiencing rapid progress can be observed from the competition between industrial sectors in small, medium to large scale industries. Along with advances in the industrial world, it cannot be denied that many problems often arise in the production process, including wear and corrosion, it is necessary to have surface treatment [1,2,3,4].…”
Section: Introductionmentioning
confidence: 99%